تعزيز الالتزام التنظيمي لدى الموظفين في المؤسسات الصحية من خلال مدخل إدارة التغيير دراسة حالة - مؤسسة عمومية للصحة الجوارية بولاية بشار: Strengthening the organizational commitment of employees in health institutions through the change management portal - Study of the case of a public institution for neighbourhood health in Bechar province- - حاجي كريمة (Journal of North African Economies, 2025)
The attention to organizational commitment is one of the most important approaches that change management studies and is especially important in the field of health because it relates to the person and touches on the most important aspects of his life. Therefore, the health institution is the most institution that needs to strengthen the organizational commitment. This research aims to highlight the most important means of enhancing organizational commitment for employees in Algerian public health institutions, one of its main results was that managing change in the human element, technological development, ease of systems and administrative procedures leads to employee commitment in these institutions.